(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
With vibrating Indian culture life style is changing in urban as well as rural India. Adapting changes with international standard India is growing economy in global market. Instead of diversity observed with culture, geological subgroups, languages and many more, people in India always ready to adapt new technology and research which makes life style human better each day. While urban India emerging with smart city programs, rural India is not at all losing the race. These development activities and adaptation makes Indian researcher and academician to address local problem and benefit the society. The new minds always striving to inculcate global and local research into technological development which will gradually improve human life. The improvement in the lifestyle can be majored with various parametric comparison, out of which societal improvement can be observed via socio-economic indices. Here case study of new state of India is proposed, which is analyzed though life cycle from data capturing to inference drawing. Such vital inference and finding will help government in policy making, problem finding and solving for local governance and sustainable solutions.